EXPLORING THE INTERSECTIONS OF IDENTITY: CHARACTER ANALYSIS ANITA DESAI’S SELECTED NOVELS - Vandna Hooda; Prof. (Dr) Shalini Yadav (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Anita Desai’s selected novels delve into the subtle intersections of identity through character analysis, gender dynamics, social class intricacies, and cultural identity. Characters like Bim from "Clear Light of Day," Biju from "The Inheritance of Loss," and Uma from "Fasting, Feasting" serve as conduits for exploring these themes. Bim epitomizes the gendered roles in post-colonial India, navigating familial responsibilities amidst societal shifts. Biju’s immigrant experience in the United States reflects the interplay of social class and cultural identity, highlighting fractures in societal structures. Uma’s story within a traditional Indian family delves into the constraints of gender roles and societal expectations on women, prompting reflection on autonomy and self-discovery.Unraveling the characters’ backgrounds and key life experiences deepens our understanding of Desai’s thematic contours. Their internal struggles and conflicts resonate universally, transcending cultural and geographical boundaries. Through meticulous character development and evocative prose, Anita Desai’s exploration of identity offers a profound journey into the human experience within the constraints of societal expectations and personal aspirations.